Phenotype Standardization is the Urgent Need in Genetic Association Studies of Disc Degeneration - Results of Analysis of Genetic Association of 71 SNPs with Highly Specific Phenotypes in 809 Subjects. Issue 1 (April 2016) - Rajasekaran, S.; Kanna, Rishi M.; Natesan, Senthil; Muthurajan, Raveendran; Ranjani, Veera; Cheung, Kenneth M. C.; Chan, Danny; Kao, Patrick Y. P.; Yee, Anita; Prasad, Ajoy
Introduction: Although the influence of genetics on etio-pathogenesis of disc degeneration is well recognized, there is a wide variation in the different genes observed to have association with disc degeneration. The clinical and radiographic features of disc degeneration used as phenotypes are quite variable in previously published studies. It is unclear whether the variations in genetic association studies depict variations in ethnicity or selection of phenotypes. Methods: The purpose of the study was to evaluate the allelic diversity of 71 SNPs related to six different MRI markers of lumbar degenerative disc disease (annular tear, Pfirmann's grading, Schmorl's nodes, Modic changes, Total Endplate Damage score and disc bulge) in a single study population, and analyze how genetic associations can vary in the same study subjects with the choice of phenotype, based on age and sequence of selection of study subjects. Genotyping of cases and controls was performed on Genome wide SNP array to identify potentially associated disease loci. The results from the GWAS were then used to facilitate SNP selection and genotype validation was conducted using Sequenom based genotyping. Results: The mean age of 809 subjects (M: 455, F:354) was 36.76 ± 10.8 years (range 10 – 80). Highly significant association ( p < 0.01) was observed with three SNPs of CILP for disc bulge and rs2249350 of ADAMTS5 and rs11247361IGF1R for annular tears. Significant association ( p < 0.05) was observed with polymorphisms of VDR and MMP20 for Modic changes, three SNPs of MMP20 for Schmorl's node and SNPs of CALM1 and FN1 for Pfirmann's grading. None of the SNPs had significant association with TEPS. Subgroup analysis based on age (<30, 30–40 and > 40 years) showed new set of genetic associations for all the six radiographic parameters. Similarly the population was divided into two groups based on numerical order and the association patterns completely differed as compared with the total group. Conclusions: In the same study population with DDD, SNP associations completely change when phenotypes changed. Variations in age, sequence of study subjects, number of population apart from radiographic description of DDD significantly change the genetic association. Based on current results, it is difficult to consider one set of genes as responsible for disc degeneration considering these variations. Our study results demand an urgent need for standardizing the description of DDD, phenotype selection, and study criteria for genetic association studies.